Objects of constitutional security of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article is devoted to some aspects of ensuring constitutional security, the relationship between the political and other rights of Kazakhstan citizens and the principles of the constitutional order of the Republic of Kazakhstan. The purpose of the work is to analyze the problems of the functioning of the constitutional system of the Republic of Kazakhstan and the issues of its improvement in the context of the study of some principles of ensuring social consent and political stability. In particular, religious and political extremism as one of the threats to constitutional security. The urgency of the problem is determined by the socio-political importance for the Kazakhstani state and society of the constitutional system as an unconditional component of the democratic development of the Republic of Kazakhstan. When writing the article, both general scientific and private scientific methods of research were used (dialectical, historical, comparative legal, special legal, logical). The practical significance of the article lies in the possibility of using the obtained results in improving the current legislation of the Republic ofKazakhstan on ensuring constitutional security, as well as in law enforcement practice.Key words: constitutional security, constitutional system, public consent, extremism, political rights,principles.